2010
DOI: 10.1016/j.ijdevneu.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of interneurons in the striatum and frontal cortex of mice during postnatal development

Abstract: We investigated the postnatal alterations of neuronal nuclei (NeuN)-positive neurons, parvalbumin (PV)-positive interneurons, neuronal nitric oxide synthase (nNOS)-positive interneurons, and neurotrophic factors in the mouse striatum and frontal cortex using immunohistochemistry. NeuN, PV, nNOS, nerve growth factor (NGF), and brain-derived neurotrophic factor (BDNF) immunoreactivity were measured in 1-, 2-, 4- and 8-week-old mice. Total number of NeuN-positive neurons was unchanged in the mouse striatum and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our data also showed a developmental decrease of SOM + and PV + cells in the visual cortex of En2 +/+ mice, though less pronounced than that observed in En2 −/− animals (Figure 3B). Indeed, a decrease of inhibitory interneurons in the mouse frontal cortex has been described to occur during postnatal development (Eto et al, 2010). In addition, a recent study showed that in layers II–III of the mouse primary visual cortex, PV + cell density increases from P28 to P42, and then decreases until P70 (Ye and Miao, 2013), with no change of total cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also showed a developmental decrease of SOM + and PV + cells in the visual cortex of En2 +/+ mice, though less pronounced than that observed in En2 −/− animals (Figure 3B). Indeed, a decrease of inhibitory interneurons in the mouse frontal cortex has been described to occur during postnatal development (Eto et al, 2010). In addition, a recent study showed that in layers II–III of the mouse primary visual cortex, PV + cell density increases from P28 to P42, and then decreases until P70 (Ye and Miao, 2013), with no change of total cell density.…”
Section: Discussionmentioning
confidence: 99%
“…Although maturation of type I nNOS neurons appears to precede sexual maturity in rodents (Chung et al, 2004; Eto et al, 2010), no such data are available for weakly labeled cortical NK1 neurons. Ontogenetic studies will be needed to evaluate if differences in cortical maturation contributed to the differences in distribution of weakly labeled NK1 neurons reported here.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of PV expression in these interneurons is unknown, but as these interneurons are involved in processing of primary sensory information from receptors in the skin, ablation of munc18-1 in these neurons is unlikely to produce the motor coordination defects observed in these experiments. There is also widespread expression of PV in GABAergic interneurons in the cortex and basal ganglia, but in mice relatively few neurons express PV during the first postnatal week compared with adult animals [17, 22, 24]. Generalized loss of GABAergic transmission following ablation of munc18-1 in PV-expressing interneurons may lead to increased potential for seizures in munc18-1 conditional mutants, but spontaneous seizures were not observed in our experiments.…”
Section: Discussionmentioning
confidence: 77%